Is supplementary feeding in gardens a driver of evolutionary change in a migratory bird species?. (24th September 2015) - Plummer, Kate E.; Siriwardena, Gavin M.; Conway, Greg J.; Risely, Kate; Toms, Mike P.
Abstract: Human activities are causing rapid environmental change at a global scale. Urbanization is responsible for some of the most extreme human‐altered habitats and is a known driver of evolutionary change, but evidence and understanding of these processes is limited. Here, we investigate the potential underlying mechanisms contributing to the contemporary evolution of migration behaviour in the Eurasian blackcap ( Sylvia atricapilla ). Blackcaps from central Europe have been wintering in urban areas of Britain with increasing frequency over the past 60 years, rather than migrating south to the Mediterranean. It has been hypothesized that the popularization of providing supplementary foods for wild birds within Britain may have influenced this marked migratory change, but quantifying the selective forces shaping evolutionary changes remains challenging. Using a long‐term national scale data set, we examine both the spatial distribution and interannual variation in blackcap wintering behaviour in Britain in relation to supplementary food availability and local climate. Over a 12‐year period, we show that blackcaps are becoming increasingly associated with the provision of supplementary foods in British gardens, and that the reliability of bird food supplies is influencing their winter distribution at a national scale. In addition, local climatic temperatures and broader scale weather variation are also important determinants of blackcap wintering patterns once they arrive in Britain. Based on our findings, we conclude that a synergistic effect of increased availability of feeding resources, in the form of garden bird food, coupled with climatic amelioration, has enabled a successful new wintering population to become established in Britain. As global biodiversity is threatened by human‐induced environmental change, this study presents new and timely evidence of the role human activities can play in shaping evolutionary trajectories.